Adaptive fast sliding mode fault tolerant control integrated with disturbance observer for spacecraft attitude stabilization system. (November 2019) - Guo, Bin; Chen, Yong
Abstract: In this paper, the problem of fault-tolerant control (FTC) for spacecraft attitude stabilization system with actuator fault and mismatched disturbance is investigated. A novel fault tolerant control strategy based on adaptive fast terminal sliding mode control (AFTSMC) is proposed. Firstly, a novel composite observer is proposed to estimate the disturbance, actuator efficiency factor and partial states of the system. By introducing a sliding mode observer, the bias actuator fault is reconstructed. Subsequently, in accordance with the estimated information, a novel sliding mode fault tolerant controller is designed. The proposed control scheme contains two compensators and two adaptive parameters to attenuate the mismatched disturbance, to compensate actuator fault, and to guarantee fast convergence of the system. Furthermore, the reachability of sliding motion is proved. The simulation results for the spacecraft system illustrate the effectiveness of the proposed method. Highlights: The fault-tolerant control problem is investigated for spacecraft attitude stabilization system with actuator fault and mismatched disturbance. An improved composite observer integrated with state and disturbance estimator is proposed. A novel terminal sliding mode fault tolerant control scheme is constructed to increase the convergence performance and to stabilize the system.